2016
DOI: 10.1371/journal.pone.0167250
|View full text |Cite|
|
Sign up to set email alerts
|

Relationships between Mucosal Antibodies, Non-Typeable Haemophilus influenzae (NTHi) Infection and Airway Inflammation in COPD

Abstract: Non-typeable Haemophilus influenzae (NTHi) is a key pathogen in COPD, being associated with airway inflammation and risk of exacerbation. Why some patients are susceptible to colonisation is not understood. We hypothesised that this susceptibility may be due to a deficiency in mucosal humoral immunity. The aim of our study (NCT01701869) was to quantify the amount and specificity of antibodies against NTHi in the lungs and the associated risk of infection and inflammation in health and COPD. Phlebotomy, sputum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 39 publications
2
38
1
Order By: Relevance
“…Severe infections are often associated with chronic lung diseases, like severe asthma and chronic obstructive pulmonary disease (COPD), both of which are not only associated with neutrophilia and increased LL-3716 17 but also a dysbiosis of the lung microbiome,18 with increased abundance of Proteobacteria spp and non-typeable Haemophilus influenzae (NTHi) in particular. IL-1β is already increased in the lungs of patients with COPD who are colonised with NTHi,19 and compellingly in a longitudinal cohort of patients with COPD, we observed that NTHi colonisation increased the risk of a viral infection being associated with an exacerbation compared with the presence of virus alone 20. NTHi is also frequently detected in the sputum of hospitalised patients with pneumonia 21.…”
supporting
confidence: 51%
“…Severe infections are often associated with chronic lung diseases, like severe asthma and chronic obstructive pulmonary disease (COPD), both of which are not only associated with neutrophilia and increased LL-3716 17 but also a dysbiosis of the lung microbiome,18 with increased abundance of Proteobacteria spp and non-typeable Haemophilus influenzae (NTHi) in particular. IL-1β is already increased in the lungs of patients with COPD who are colonised with NTHi,19 and compellingly in a longitudinal cohort of patients with COPD, we observed that NTHi colonisation increased the risk of a viral infection being associated with an exacerbation compared with the presence of virus alone 20. NTHi is also frequently detected in the sputum of hospitalised patients with pneumonia 21.…”
supporting
confidence: 51%
“…At the level of the target tissue, it seems intuitive that specific antibodies are an important contributor to local host defense and that their absence might contribute to chronic infection. A study of specific antibodies against non-typeable Haemophilus influenzae in COPD patients with frequent exacerbations and positive cultures for this organism showed decreased total IgG (p = 0.0068) and specific antibodies in bronchoalveolar lavage (p = 0.043) [45]. However, we do not know how often antibody deficiency contributes to COPD in clinical practice.…”
Section: Deficient Humoral Immunity In Copdmentioning
confidence: 80%
“…Respiratory infections are associated with the majority of COPD exacerbations and their severity, especially for those with viral/bacterial coinfection . In the AECOPD patients' airway, a large number of pathogen‐specific antibodies can be found, indicating the activity of immune reaction . Because of the immune response, the level of Th1 was reduced, but the level of Th2 occupied dominant position in delayed allergy.…”
Section: Discussionmentioning
confidence: 99%
“…16 In the AECOPD patients' airway, a large number of pathogen-specific antibodies can be found, indicating the activity of immune reaction. 17 Because of the immune response, the level of Th1 was reduced, but the level of Th2 occupied dominant position in delayed allergy. Oppositely, the level of Th2 cells in remission was decreased because of the treatment, while Th1 cells were increased in cellular immunity.…”
Section: Discussionmentioning
confidence: 99%